A Pilot Study to Examine Retailer Compliance Before and After Tobacco 21 in New Jersey - Mary Hrywna; Christopher Ackerman; Cristine D. Delnevo (New Prairie Press, 2022)
Despite rapid diffusion of Tobacco 21 (T21) laws in the last several years, research examining T21 compliance remains limited. This pilot study examined retailer compliance with carding before and after T21 as well as sales violations after T21 in New Jersey. A 19-year-old buyer made alternating cigar and cigarette purchase attempts in 15 licensed tobacco retailers weekly for five weeks before and 10 weeks following the T21 effective date for a total of 222 visits. We analyzed carding pre and post T21 and sales violations post T21, by store and product type. Failure to card declined post T21 (81.3% to 69.4%), particularly for cigarettes, but not cigars. Overall, 63.3% of retailers sold tobacco to the underage buyer post T21. Following New Jersey's T21 law, compliance with carding improved, but underage sales persisted. Future research examining T21 compliance should consider using a familiarity protocol to mimic real word conditions.